Economia compartilhada: características empreendedoras do provedor - Santos, Glauco Dias dos (2020)
Digital technologies are expanding people's options for obtaining goods and services. Shared economy platforms present themselves as a solution with considerable growth potential in the coming years. They arise to connect people looking for a good or service with the platform (B2C) or with people (P2P) that offer it. Despite successful cases of shared economy platforms, there are many cases of failure. The literature presents studies focused on the challenges of the platform to create and expand its network of customers and providers, lock-in, legal and regulatory issues, motivations and barriers to membership and what influences confidence in the use of the platform. In the P2P case, there is an unbalanced relationship between the parties. The platform acts to connect and manage the community, acting to ban members who have had a bad evaluation or to act in cases of conflict and to guide on mapped processes. However, the platform acts only as an orchestrator, and the provider, owner of the product or service, ends up assuming a large part of the business risk, a perspective rarely addressed in the literature. In this context, this applied work was developed seeking to identify entrepreneurial characteristics of personality and human capital that are desired for providers that participate in a shared economy platform. An exploratory case study was conducted using public secondary data from a shared economy platform of the type P2P carsharing. Through a qualitative analysis of four public interviews given by Tamy Lin, the CEO of Moobie, available on the web and an interview with a professional who works in the recovery of vehicles from car rental companies, this study made a comparison between the traditional car rental business (through car rental companies) and the offered by a P2P carsharing platform, observing the respective risks and responsibilities in each scenario per actor. It was possible to observe several characteristics that help the provider, such as business knowledge, the ability to manage risks and have a network of relationships. This approach can be used to understand other shared economy platforms from the provider's point of view, a central figure in P2P cases.